Association of Organizational Learning with Leadership, Job Satisfaction and Engagement in an EFL Setting - YASTIBAŞ, Ahmet Erdost; BATURAY, Meltem Huri (JET (Journal of English Teaching), 2021)
The present study investigated the relationship between organizational learning, department leadership, teacher leadership, job satisfaction and engagement in a higher education language institution. It was designed as a quantitative study. 96 Turkish English language instructors participated in the research. The data were collected in a Turkish higher education language institution. Four scales were used to collect data. The data were analyzed through samples t-test, one-way ANOVA, Pearson’s r correlation, and multiple regression analysis. The findings indicated that there were not statistically significant differences between participants in terms of their genders, Bachelor’s degrees, status of masters of art, and the departments they worked, but of their teaching experiences with regard to organizational learning, department leadership, teacher leadership, job satisfaction, and engagement. They also showed that there were statistically significant relationships among engagement, job satisfaction, teacher leadership, organization learning, and department leadership. Besides, they revealed that department leadership and job satisfaction could predict organizational learning positively and explain the 74% of the variance in organizational learning. Department leadership can have a central role in promoting organizational learning in a higher education language institution through creating a working environment which supports and values teacher leadership, so teachers/instructors can feel more engage and satisfied.